Luzifers-Ab schied from Samstag aus Licht. Stockhausen and the Italian affair - Draus, Agnieszka (Interdisciplinary Studies in Musicology, 2018)
The homeland of Leonardo and Palestrina, Dante and Eco, Verdi and Fellini became crucial for the reception of music of one of the most controversial, and at the same time innovative composers of the second half of the 20th century, a German artist, Karlheinz Stockhausen. The genius- and visionary-bearing nation opened itself to the new musical art, and appointed the author of Hymnen to be the coryphaeus of that art. This fascination transformed into a desire to better present the composer’s personality to a wider audience. Many of the most recent Stockhausen’s compositions were created as a response to numerous Italian orders, including ArtArche’s from Milan or Massimo Simonini’s from the Angelica Foundation, many of them were performed for the first time in the most magnificent works of Italian architecture, for example the Milan cathedral. The stage premieres of Donnerstag, Samstag and Montag aus Licht took place in Milan’s La Scala, with the creative participation of such celebrities as a theatre and opera director, Luca Ronconi and an architect, Gae Aulenti, famous most of all for her contemporary designs of Parisian museum buildings, and in the project of Licht - for scenography. In 2007 Stockhausen’s music filled 25. Rassegna di Nuova Musica in Macerata Teatro Lauro Rossi; during two days the most famous electronic compositions were presented: Mittwochs-Gruss, Cosmic Pulses, Gesang der Jünglinge, Telemusik and Kontakte. Lucifer’s Farewell is the last - and the most “Italian” - scene devoted to this character of the opera - Samstag aus Licht. It was finished in August 1982 upon the order of Associazione Sagra Musicale Umbra in Perugia, celebrating the 800th birth anniversary of St. Francis of Assisi. The opening night took place on 18th September that same year in Chiesa di San Rufino in Assisi. In the composition Stockhausen interprets the text of Lodi delle virtu (A Salutation of the Virtues) of the little poor man in the original wording of the Italian language. The article is an interpretation both text and music of Luzifers Abschied within a wide range of problem context of the whole stage cycle Licht (‘Light’) by Karlheinz Stockhausen.